Exploring AI-mediated linguistic and cognitive support for non-native English speakers in English-only higher education - Tien, Ching-Yi; Haji-Othman, Noor Azam (Universitas Ahmad Dahlan, 2025)
The release of ChatGPT by OpenAI in 2022 marked a major milestone, beginning a new phase in how artificial intelligence (AI) is used in education and transforming the way students access and engage with academic resources. This study explores how non-native English-speaking students handle the language challenges of content-area courses in higher education when instruction is focused solely on professional subjects in an English-only setting, with limited explicit language support to improve English skills. Using a sample of undergraduate students (N = 63), this research examines differences in AI tool usage, perceptions, and outcomes based on gender, nationality, major, and year of study. Independent samples t-tests and one-way ANOVA were performed on variables that measure perceived language learning benefits, cognitive skill development, creative tool use, and the overall effectiveness of AI tools. Open-ended questions provided qualitative data for this study. The findings show that AI and Generative AI tools meet students’ linguistic needs, address cognitive demands, support personalized learning, enhance understanding of subject material, and improve academic performance. Contrary to earlier research suggesting male students are more proficient with AI, this study finds that female students are more likely to view AI tools as beneficial for integrating thinking and higher-order cognitive skills. The study also discusses potential challenges related to AI use and notes its methodological limitations.